Torque and Power Testing of the Pelton Turbine - Dedi Wardianto; Irwan Anwar; Afdal (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2021)
Energy sources that can be renewed in Indonesia according to Asean energy sources, one of which is microhydro that uses water as a source of energy from a turbine. The potential energy of water is converted into kinetic energy in the nozzles. The water coming out of the nozzle that has a high speed hits the turbine blade. After hitting the blade direction the flow velocity changes so that the momentum changes (impulses) so that the turbine wheel will rotate. Pelton Turbines are impulse turbines which consist of a set of road blades that are rotated by a jet of water sprayed from one or more devices called nozzles. Pelton Turbine is one of the most efficient and suitable types of water turbines used for high head and small flow discharge. Pelton turbines have several advantages including turbine efficiency which is relatively stable at various changes in flow discharge. The purpose of this writing is to find out and provide insight into the torque and power of the Pelton turbine and the effect on the valve openings that are varied.